Kalani Ying Wong COVID-19 21st Birthday Photograph - Wong, Kalani Ying::::::::: (2022)
Public health student Kalani Ying Wong's family poses around a cake to celebrate Kalani's 21st Birthday. The contributor writes, "On November 8, 2020, I turned 21, and although my birthday looked different this year with social distancing and everyone wearing masks, I still count it as a blessing that I got to share this special moment with my family. This year has been challenging for all of us, but in these times, I try my best to find something that brings me joy and makes me smile every day! I am incredibly grateful to have my family, friends, classmates, and professors keeping sane and reminding me that they are only one message or call away whenever I feel lonely."